A qualitative exploration of self-reported unmet need one year after stroke. Issue 20 (24th September 2016) - Shannon, Rosie L.; Forster, Anne; Hawkins, Rebecca J.
Abstract: Purpose: Stroke survivors consistently report longer-term problems after stroke, suggesting their needs are not being met. We developed a questionnaire to identify stroke-survivor unmet needs. Preliminary questionnaire testing showed that despite residual impairment, nearly one third of respondents reported no/low unmet need. This qualitative study aims to gain insight into why stroke survivors report low/no unmet needs. Method: People who self-reported zero or one unmet need were purposively sampled and semi-structured interviews were conducted with 10 participants. Identification and management of current problems were discussed and thematic analysis was undertaken. Results: Participants did not report having unmet need. Despite this, all participants identified current issues or problems. Living with problems while reporting no/low unmet need is explained through: acceptance of changed circumstances; making comparisons with other people and circumstances; valuing pride, determination or independence; and viewing issues in the context of their expectations and experiences of services. Additionally, all participants were receiving some support. Conclusions: Self-identification of unmet needs is complex. Further investigation could explore the factors which enable stroke survivors to appropriately identify and experience no unmet needs, and whether these could be applied to reduce unmet needs of others. Implications for Rehabilitation: Despite self-reporting no/low unmet need, survivors of stroke may still be experiencing difficulties in their daily lives. Stroke-survivor-identified low unmet need is influenced by complex factors including: acceptance; expectations of services; and comparisons with other people, which Health and Social Care professionals have a role in understanding. Health professionals could assess unmet need by using tools as a guide, supported by individual conversation. Factors which enable some stroke survivors to appropriately identify and experience no/low unmet need could be further explored, and considered as strategies to reduce unmet needs of others.